Targeting NK Cell Inhibitory Receptors for Precision Multiple Myeloma Immunotherapy - Alfarra, Helmi; Weir, Jackson; Grieve, Stacy; Reiman, Tony (Frontiers in Immunology, 2020)
Innate immune surveillance of cancer involves multiple types of immune cells including the innate lymphoid cells (ILCs). Natural killer (NK) cells are considered the most active ILC subset for tumor elimination because of their ability to target infected and malignant cells without prior sensitization. NK cells are equipped with an array of activating and inhibitory receptors (IRs); hence NK cell activity is controlled by balanced signals between the activating and IRs. Multiple myeloma (MM) is a hematological malignancy that is known for its altered immune landscape. Despite improvements in therapeutic options for MM, this disease remains incurable. An emerging trend to improve clinical outcomes in MM involves harnessing the inherent ability of NK cell to kill malignant cells by recruiting NK cells and enhancing their cytotoxicity towards the malignant MM cells. Although there are different approaches to activate and unleash NK cells, a promising option involves blocking NK cell IRs. The clinical success of PD-1 and CTLA-4 blockade in cancer treatment has led to more interest in IRs and their cognate ligands, including the production of several blocking antibodies. Relevant NK cell IRs that are attractive candidates for checkpoint blockade include KIRs, NKG2A, LAG-3, TIGIT, PD-1, and TIM-3 receptors. Investigating NK cell IRs as pathogenic agents and therapeutic targets could lead to promising applications in multiple myeloma (MM) therapy. The purpose of this review is to describe the critical role of NK cell IRs and their cognate inhibitory ligands in MM biology and to discuss their potential as novel therapeutic targets for precision MM immunotherapy.